Transurethral Resection of Prostate Abscess: Is It Different from Conventional Transurethral Resection for Benign Prostatic Hyperplasia? - Goyal, Neeraj Kumar (Hindawi Publishing Corporation, 2013)
Purpose. To present our experience of prostate abscess management by modified transurethral resection (TUR) technique. Methods. Seventeen men with prostate abscess undergoing TUR between 2003 and 2011 were retrospectively analyzed. Details of demography, surgical procedures, complications, and followup were noted. Results. With a mean age of 61.53 ± 8.58 years, all patients had multifocal abscess cavities. Initially, 6 men underwent classical TUR similar to the technique used for benign prostatic enlargement (group 1). Next, 11 men underwent modified TUR (group 2) in which bladder neck and anterior zone were not resected. The abscess cavities resolved completely, and no patient required a second intervention. One patient in group 1 and three in group 2 had postoperative fever requiring parenteral antibiotics (P = 0.916). Three patients in group 1 had transient urinary incontinence, whereas none of the patients in group 2 had this complication (P = 0.055). Four and five men in group 1 and 2 reported retrograde ejaculation, respectively (P = 0.740). Conclusion. The modified technique of prostate resection edges over conventional TURP in the form of reduced morbidity but maintains its high success rate for complete abscess drainage. It alleviates the need for secondary procedures, having an apparent advantage over limited drainage techniques. Use of this technique is emphasized in cases associated with BPH and lack of proper preoperative imaging.